Effects of water stress on the development of banana xanthomonas wilt disease. (8th September 2014) - Ochola, D.; Ocimati, W.; Tinzaara, W.; Blomme, G.; Karamura, E. B.
<x xml:space="preserve">Abstract</x> Water quantity and distribution plays a significant role in determining the productivity of crops and the outcome of many host–pathogen interactions in natural plant populations. In the present study, tissue culture plants of the East African highland banana cultivar Mbwazirume were established in a screenhouse to mimic drought conditions in the field and so investigate the effects of water stress on the development of banana xanthomonas wilt (BXW) caused by the bacterium Xanthomonas campestris pv. musacearum (Xcm). In the absence of host resistance, all inoculated banana plants succumbed to Xcm infection and symptoms were expressed, on average, 14 days post‐inoculation (dpi). Water stress effects were significant (P < 0·05) for disease incubation period, and significant (P < 0·001) for incidence and severity. Data revealed that BXW development is hastened by the combined effect of water stress before and after inoculation compared to when plants are stressed only before inoculation or maintained stress‐free (SF). A twofold increase in evaluated disease parameters suggests that both timing of infection and duration of exposure to water stress are important in determining the shortened resident phase of Xcm to multiply and rapidly spread in the vascular tissues of the banana. This study has shown that water‐stressed banana plants are physiologically weak and hence more vulnerable to Xcm infections. This may be of relevance to the effect of future climate change on banana production.